Diversity, distribution and organic substrates preferences of microbial communities of a low anthropic activity cave in North-Western Romania - Bogdan, Diana Felicia; Baricz, Andreea Ionela; Chiciudean, Iulia; Bulzu, Paul-Adrian; Cristea, Adorján; Năstase-Bucur, Ruxandra; Levei, Erika Andrea; Cadar, Oana; Sitar, Cristian; Banciu, Horia Leonard; Moldovan, Oana Teodora (Frontiers in Microbiology, 2023)
Karst caves are characterized by relatively constant temperature, lack of light, high humidity, and low nutrients availability. The diversity and functionality of the microorganisms dwelling in caves micro-habitats are yet underexplored. Therefore, in-depth investigations of these ecosystems aid in enlarging our understanding of the microbial interactions and microbially driven biogeochemical cycles. Here we aimed at evaluating the diversity, abundance, distribution, and organic substrate preferences of microbial communities from Peștera cu Apă din Valea Leșului (Leșu Cave) located in the Apuseni Mountains (North-Western Romania). To achieve this goal, we employed 16S rRNA gene amplicon sequencing and community-level physiological profiling (CLPP) paralleled by the assessment of environmental parameters of cave sediments and water. Pseudomonadota (synonym Proteobacteria) was the most prevalent phylum detected across all samples whereas the abundance detected at order level varied among sites and between water and sediment samples. Despite the general similarity at the phylum-level in Leșu Cave across the sampled area, the results obtained in this study suggest that specific sites drive bacterial community at the order-level, perhaps sustaining the enrichment of unique bacterial populations due to microenvironmental conditions. For most of the dominant orders the distribution pattern showed a positive correlation with C-sources such as putrescine, γ-amino butyric acid, and D-malic acid, while particular cases were positively correlated with polymers (Tween 40, Tween 80 and α-cyclodextrin), carbohydrates (α-D-lactose, i-erythritol, D-mannitol) and most of the carboxylic and ketonic acids. Physicochemical analysis reveals that sediments are geochemically distinct, with increased concentration of Ca, Fe, Al, Mg, Na and K, whereas water showed low nitrate concentration. Our PCA indicated the clustering of different dominant orders with Mg, As, P, Fe, and Cr. This information serves as a starting point for further studies in elucidating the links between the taxonomic and functional diversity of subterranean microbial communities.